EMS dose optimization to develop large-scale mutants in rapeseed (Brassica L.) (Bangladesh Journal of Botany, 2024)
Mutation breeding is a great way to create variation in plant genomes, and Ethyl Methane Sulphonate (EMS) is commonly used for this purpose. To determine the optimum dose of EMS for developing large-scale mutants, B. napus and B. rapa (BARI Sarisha-18 and BARI Sarisha-20, respectively) were treated using six different concentrations (T0:0%, T1:0.1%, T2:0.2%, T3:0.3%, T4:0.4%, and T5:0.5%) of EMS. For B. napus, 100% germination was observed in T0, T1, and T2, while for B. rapa, it was in T0 and T1 treatment. The highest survival rates, 70% for B. napus and 60% for B. rapa, were recorded at T1 treatment. Morphological traits such as leaf number, shoot and root length, and fresh and dry weights was found highest in T1 treatment for both species. The LD50 was calculated at 0.16% for B. napus and 0.18% for B. rapa, indicating the ideal dose for generating a large number of mutants.Bangladesh J. Bot. 53(4): 1077-1080, 2024 (December)